What kind of state? what kind of equality? (UN ECLAC SantiagoCL, 2010)
Analyses the progress of gender equality in the region 15 years after the approval of the Beijing Platform for Action, 10 years after the drafting of the Millennium Development Goals and 3 years after the the adoption of the Quito Consensus at the 10th Session of the Regional Conference in 2007. Also examines the achiements made and challenges faced by governments in light of the interaction between the State, the market and families as social institutions built on the foundation of policies, laws, and customs and habits which together, establish the condictions for renewing or perpetuating gender and social hierarchies.
Keywords: WOMEN